Conflict monitoring and attentional adjustment during binocular rivalry. (23rd December 2021) - Drew, Alice; Torralba, Mireia; Ruzzoli, Manuela; Morís Fernández, Luis; Sabaté, Alba; Pápai, Márta Szabina; Soto‐Faraco, Salvador
Abstract: To make sense of ambiguous and, at times, fragmentary sensory input, the brain must rely on a process of active interpretation. At any given moment, only one of several possible perceptual representations prevails in our conscious experience. Our hypothesis is that the competition between alternative representations induces a pattern of neural activation resembling cognitive conflict, eventually leading to fluctuations between different perceptual outcomes in the case of steep competition. To test this hypothesis, we probed changes in perceptual awareness between competing images using binocular rivalry. We drew our predictions from the conflict monitoring theory, which holds that cognitive control is invoked by the detection of conflict during information processing. Our results show that fronto‐medial theta oscillations (5–7 Hz), an established electroencephalography (EEG) marker of conflict, increases right before perceptual alternations and decreases thereafter, suggesting that conflict monitoring occurs during perceptual competition. Furthermore, to investigate conflict resolution via attentional engagement, we looked for a neural marker of perceptual switches as by parieto‐occipital alpha oscillations (8–12 Hz). The power of parieto‐occipital alpha displayed an inverse pattern to that of fronto‐medial theta, reflecting periods of high interocular inhibition during stable perception, and low inhibition around moments of perceptual change. Our findings aim to elucidate the relationship between conflict monitoring mechanisms and perceptual awareness. Abstract : We report evidence for the involvement of cognitive monitoring mechanisms (conflict detection and attention engagement) during binocular rivalry. We observed that oscillatory activity in fronto‐medial theta (5–7 Hz) increased and parieto‐occipital alpha (8–12 Hz) decreased right before perceptual alternations with this pattern reversing following perceptual switches. Our results suggest that conflict mechanisms and adjustments play complementary roles during fluctuations of perceptual awareness.